Technologies for Opioid Use Disorder Management: Mobile App Search and Scoping Review - Nuamah, Joseph; Mehta, Ranjana; Sasangohar, Farzan (JMIR Publications, 2020)
BackgroundAdvances in technology engender the investigation of technological solutions to opioid use disorder (OUD). However, in comparison to chronic disease management, the application of mobile health (mHealth) to OUD has been limited. ObjectiveThe overarching aim of our research was to design OUD management technologies that utilize wearable sensors to provide continuous monitoring capabilities. The objectives of this study were to (1) document the currently available opioid-related mHealth apps, (2) review past and existing technology solutions that address OUD, and (3) discuss opportunities for technological withdrawal management solutions. MethodsWe used a two-phase parallel search approach: (1) an app search to determine the availability of opioid-related mHealth apps and (2) a scoping review of relevant literature to identify relevant technologies and mHealth apps used to address OUD. ResultsThe app search revealed a steady rise in app development, with most apps being clinician-facing. Most of the apps were designed to aid in opioid dose conversion. Despite the availability of these apps, the scoping review found no study that investigated the efficacy of mHealth apps to address OUD. ConclusionsOur findings highlight a general gap in technological solutions of OUD management and the potential for mHealth apps and wearable sensors to address OUD.